Investigation of the base oil properties in optimizing the demulsification - C. M., Low; A. N., Ilia Anisa; B. L., Chua; N. H., Abdurahman (Institute of Physics, 2022)
In this research, the correlation of the physical properties from different types of base oil- Group I and Group II base oils - to the demulsification process with variables such as mixing speed (500-1500 rpm), water content (20-80%) and volume of formulated surfactant (1 - 5 ml) were investigated. The water-in-oil emulsion was prepared using a formulated surfactant, and the demulsification was observed via a Bottle Test method. The optimization of demulsification was obtained from the correlation of the respective variables using the Central Composite Design (CCD) for Response Surface Methodology (RSM). Results showed that the Group I base oil emulsions have a lower viscosity and higher density than the Group II base oil, which has higher emulsion stability. The higher demulsification was observed by reducing the mixing speed, increasing the water content, and reducing the volume of the formulated surfactant for both groups of the base oil. The optimum of the water separation w obtained from the Group I base oil was 46.73% at 515 rpm, 76% water content, and 1 ml volume of the formulated surfactant. Meanwhile, 99.29% of water separation was found for the Group II base oil at 520 rpm, with 75% water content and 2 ml volume of the formulated surfactant.